Phytochemical Screening and Antimicrobial Activity of Roselle (Hibiscus sabdariffa L.) Flower Extract Against Aeromonas hydrophila - Bariyyah, Sitti Khairul; Prajitno, Arief; Yuniarti, Ating (Graduate School, Universitas Brawijaya, 2019)
Medicinal plants as an antimicrobial agent may provide an alternative way to replace the use of antibiotics to control disease agents in aquaculture. Roselle flowers (Hibiscus sabdariffa L.) has been used in many sectors as a source of functional food, natural coloring agents as well as antimicrobial agents. The objectives of this study were to evaluate the phytochemical compound in methanolic extract of roselle flower and their antimicrobial activity against Aeromonas hydrophila. The phytochemical composition of roselle flower was evaluated using phytochemical screening and FTIR. While the antimicrobial activity was performed by using the disc diffusion agar and co-culture with A. hydrophila. The results of phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, steroids, triterpenoids, and tannins. The results of FTIR revealed that Roselle flower extract had the main phenolic compounds. The result of disc diffusion and co-culture method indicated that the roselle flower extract had antibacterial activity against A. hydrophila. This antibacterial activity depended on the concentration applied.Keywords: antibiotics, Co-culture, Disk diffusion, flavonoid, Hibiscus sp.